(untitled) (Journal of the Bangladesh Agricultural University, 2024)
The carp culture in Bangladesh has become a prominent factor in the country’s aquaculture industry, economics, and food security. The primary goals of the research were to assess the extent of fish farmers’ knowledge in practicing major carp culture, and to determine the influential factors that may impact the knowledge of the fish farmer in practicing major carp culture. Data were collected from three unions named Digpaith, Sahabajpur, and Titpalla of Jamalpur Sadar Upazila (sub-district) under Jamalpur district from June to July 2023 purposefully. Personal interviews were conducted with 102 randomly chosen carp fish farmers. The level of knowledge was assessed using revised Bloom’s taxonomy, which employs six levels of the cognitive domain. The main finding of the study highlights that 54.9% of the fish farmers were identified as having a moderate level of knowledge, followed by 45.1% with a poor level of knowledge. Multiple linear regression analysis revealed that, out of the 12 socioeconomic characteristics of farmers, education, training, extension contact, and organizational involvement significantly influenced farmers’ knowledge. The stepwise multiple regression analysis showed that factors such as education (47.1%), training received (10.7%), extension contact (2.8%), and organizational involvement (2.1%) collectively account for 62.7% of the observed variations. The Department of Fisheries (DoF), Bangladesh Fisheries Research Institute (BFRI), and other non-governmental organizations (NGOs) need to take appropriate actions including need-based trainings, demonstrations, extension supports etc. to enhance the knowledge of fish farmers in practicing major carp culture. J Bangladesh Agril Univ 22(4): 480-489, 2024